The Role of Land Conservation in Plantation Management - A ABAS IDJUDIN (Indonesian Center for Agriculture Land Resource Development, 2011)
The main problem of agricultural activities in the steep slope upland area if without adequate soil conservation practices is that it will results in soil erosion. Soil erosion causes agricultural land degradation which reduces the physical, chemical, and biological soil roperties and decreases land productivities. Soil erosion is very harmful to agricultural land productivities, because loss of the fertile topsoil in a relatively short time causes decrease of fertility and productivity of the soils. The role of conservation techniques are the way of soil conservation, which have three principles of definitions, i.e. a) to protect the soil against soil degradation, b) to improve the degraded soil, and c) to make the soil more fertile. Soil conservation practice in the field have used two methods i.e. mechanical conservation methods and vegetative conservation methods. Mechanical conservation method is the earth embankments constructed across the slope to intercept surface run off and to protect soil erosion (soil cultivation along the contour, terraces constructed, contour bank, waterways ditch, drop structure, silt pit, checkdam, gully plug, etc). While the vegetative methode are reducing the kinetic energy of the raindrops on the soil surface, reducing the run off velocity, increasing infiltration rate and reducing soil water contents. The effectiveness of soil conservation techniques in uplands area on the the soil erosion and the land productivity is different in each location. This is because of the difference of the land capability (site specific, soil behavior and properties, and the climate). Farmers’ motivation as the user of the soil conservation technologies is included as one on the determinant factors of the successfulness in improving degraded upland and in increasing land productivity.